2014
DOI: 10.1371/journal.pone.0093365
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Fast Change-Point Detection on Simulated Time Series and Electrocardiogram Data

Abstract: Although Kolmogorov-Smirnov (KS) statistic is a widely used method, some weaknesses exist in investigating abrupt Change Point (CP) problems, e.g. it is time-consuming and invalid sometimes. To detect abrupt change from time series fast, a novel method is proposed based on Haar Wavelet (HW) and KS statistic (HWKS). First, the two Binary Search Trees (BSTs), termed TcA and TcD, are constructed by multi-level HW from a diagnosed time series; the framework of HWKS method is implemented by introducing a modified K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Not surprised, the method based on KST created the FCNs with smaller false positive and false negative rates than those from KS and T methods. It might be explained by that KST had better ability for detection of the fluctuations from each of the time series segments, which has been addressed in our previous work [19][20][21]. Some examples of the visualized FCNs are shown in figure 3.…”
Section: Implementation and Experimentsmentioning
confidence: 85%
See 1 more Smart Citation
“…Not surprised, the method based on KST created the FCNs with smaller false positive and false negative rates than those from KS and T methods. It might be explained by that KST had better ability for detection of the fluctuations from each of the time series segments, which has been addressed in our previous work [19][20][21]. Some examples of the visualized FCNs are shown in figure 3.…”
Section: Implementation and Experimentsmentioning
confidence: 85%
“…A review of these algorithms can be found in [18]. In our previous study on time point change detection [19][20][21], we analyzed how KS and T could be used for calculating the fluctuations of a time series. In this study, we took the advantages of KS and T statistic for detection of the maximum fluctuations in the segments of a time series and built a fluctuation correlation network (FCN) based on the fluctuation data matrices that was created from a combined method with KS and T statistics (KST).…”
Section: Introductionmentioning
confidence: 99%
“…The normalized TPD, FND, TND and FPD can be represented as true positive distant rate (TPDR), positive error distance rate (PEDR), true negative distance rate (TNDR) and negative error distance rate (NEDR). These values can be calculated by formula (5) to formula (8). Basically, the distance between the start point and the t-CP and the distance from the t-CP to end point of each tested time series are both normalized to 1, and the normalized t-CP position for each time series will match to the same point.…”
Section: Methodsmentioning
confidence: 99%
“…This application would allow appropriate staff to be alerted of changes in a patient's medical situation and to provide on-time treatment [6,7]. CPD models utilize the algorithms that cover the fields of data mining, statistics, and computer science, including parametric and nonparametric methods [8,9,10,11]. Each CPD algorithm can be assessed from the aspect of detection accuracy, computational cost or whether it can be a real time detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation